Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
x = 0, y = 2
Step-by-step explanation:
Substitute the first equation into the second equation so 3x + 3(x+2) = 6. Simplify this to get x = 0. Plug x = 0 back into the first equation to get y = 2.
Answer:
x = 0, y = 2
Step-by-step explanation:
y = x + 2
3x + 3y = 6
3x + 3(x + 2) =6
3x + 3x +6 = 6
6x = 0
x = 0
y = x + 2 = 0 + 2 = 2
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.